2021
DOI: 10.1186/s12891-021-04618-6
|View full text |Cite|
|
Sign up to set email alerts
|

Simulated weightbearing computed tomography for verification of radiographic staging of varus ankle osteoarthritis: a cross-sectional study

Abstract: Background Varus ankle osteoarthritis is classified using only weightbearing anteroposterior ankle radiographs; however, sagittal ankle alignment may also affect the position and extent of joint space obliteration. We hypothesized that the sagittal alignment of the ankle may also affect the position and extent of joint space obliteration visible on the coronal section; therefore, we identified the sites of joint space obliteration in patients with stage 3 varus ankle osteoarthritis for comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The amount of pressure was determined to be 300 N according to the instrument manual. 7,8,10,11,16 Cross-sectional areas of the tibia, 50 mm from the tibial plafond, were adjusted in the axial plane on the CT to align all the scans (Figure 1). A perpendicular line was dropped from the central point of the axial tibial slice, 1 cm from the tibial plafond, and the point at which it met the ground was regarded as the origin.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of pressure was determined to be 300 N according to the instrument manual. 7,8,10,11,16 Cross-sectional areas of the tibia, 50 mm from the tibial plafond, were adjusted in the axial plane on the CT to align all the scans (Figure 1). A perpendicular line was dropped from the central point of the axial tibial slice, 1 cm from the tibial plafond, and the point at which it met the ground was regarded as the origin.…”
Section: Methodsmentioning
confidence: 99%
“…Author details 1 Department of Orthopedic Surgery, Nara Medical University, 840 Shijo, Kashihara, Nara 634-8522, Japan. 2 Department of Orthopedics, Prince of Songkla University, 15 Karnjanavanich Road, Hat Yai, Songkhla 90110, Thailand.…”
Section: Open Accessmentioning
confidence: 99%
“…At the same time, in the study of ankle OA, we should not be limited to the ankle, and the study of the force line of lower limbs is also extremely important. Some scholars have found that the TLS is greater or smaller will lead to subluxation or anterior dislocation of the talus, and change the stress distribution of the ankle, thus leading to ankle arthritis [14]. Therefore, we wondered whether the changes in the surface shape of the DTS might be associated with changes in ankle joint stress, leading to the occurrence of ankle arthritis.…”
Section: Introductionmentioning
confidence: 98%